When is capital enough to get female microenterprises growing? Evidence from a randomized experiment in Ghana. - Fafchamps, M; McKenzie, D; Quinn, S; Woodruff, C (CSAE (University of Oxford), 2011)

(untitled)
We randomly gave cash and in-kind grants to male and female-owned microenterprises in urban Ghana. We find two striking results which contrast with a similar experiment in Sri Lanka. First, we find large average treatment effects of the in-kind grants for both female and male-owned enterprises. However, while the average increase in profits from in-kind grants to females is high, the gain in profits is almost zero for women with initial profits below the median. Second, for women we strongly reject equality of the cash and in-kind grants, with only the in-kind grants leading to business profits growing. The results for men also suggest a lower impact of cash, but are less robust. The cash grants seem to end up going to household expenses and transfers. We then investigate whether it is self-control or external pressure driving this difference between the effects of cash and in-kind grants, and find more support for a lack of self-control leading the cash to be spent than from external pressure from others. The results show that restrictions on the form that capital comes in can matter a lot for determining the likelihood of microenterprise growth.